THE OVERVIEW OF FACTORS ASSOCIATED WITH THE INCIDENCE OF ANEMIA IN PREGNANT WOMEN AT LEMPAKE HEALTH CENTER IN SAMARINDA - Wahyuni, Tiara; Tripertiwi, Sucita; Hayati, Ida; Meihartati, Tuti (HEARTY, 2026)
Anemia in pregnant women is a common health problem with a high prevalence in both Indonesia and worldwide. This condition has serious impacts on both the mother and fetus, ranging from the risk of preterm delivery, low birth weight, to an increased maternal and perinatal mortality rate. WHO data show that 35.5% of pregnant women globally experience anemia, while the prevalence in Indonesia reaches 48.9% and in East Kalimantan as high as 87%. In Samarinda City, Lempake Public Health Center ranks third among 26 health centers in terms of anemia cases in pregnant women. The factors associated with anemia during pregnancy remain inconsistent across studies, making this research important to conduct. To describe the factors associated with the incidence of anemia among pregnant women at Lempake Public Health Center, Samarinda City. This study employed a retrospective cohort design with a descriptive-analytic quantitative approach. The research was conducted from January to August 2025. The population consisted of 160 pregnant women registered at Lempake Public Health Center, from which 83 respondents with complete data were selected based on inclusion criteria. Data were collected from cohort records at the health center and analyzed using univariate methods to describe the frequency distribution of each variable. The findings showed that most respondents were in the high-risk pregnancy age group (84.3%), the majority had non-risk parity (90.4%), most had normal nutritional status (91.6%), and the majority had non-risk MUAC (77.1%). The incidence of anemia was found in 20.5% of pregnant women, while 79.5% did not experience anemia.